Incidence and computed tomography findings of lenvatinib-induced pancreatobiliary inflammation: A single-center, retrospective study. Issue 35 (3rd September 2021) - Kurokawa, Ryo; Inui, Shohei; Tanishima, Tomoya; Nakaya, Moto; Kurokawa, Mariko; Ishida, Masanori; Gonoi, Wataru; Amemiya, Shiori; Nakai, Yousuke; Ishigaki, Kazunaga; Tateishi, Ryosuke; Koike, Kazuhiko; et al.
Abstract : Abstract: In this single-center retrospective study, we intended to evaluate the frequencies and characteristics of computed tomography findings of pancreatobiliary inflammation (PBI) in patients treated with lenvatinib and the relationship of these findings with treatment-planning changes. We included 78 patients (mean ± standard deviation, 69.8 ± 9.4 years, range: 39–84 years, 62 men) with hepatocellular carcinoma (n = 62) or thyroid carcinoma (n = 16) who received lenvatinib (June 2016–September 2020). Two radiologists interpreted the posttreatment computed tomography images and assessed the radiological findings of PBI (symptomatic pancreatitis, cholecystitis, or cholangitis). The PBI effect on treatment was statistically evaluated. PBI (pancreatitis, n = 1; cholecystitis, n = 7; and cholangitis, n = 2) was diagnosed in 11.5% (9/78) of the patients at a median of 35 days after treatment initiation; 6 of 9 patients discontinued treatment because of PBI. Three cases of cholecystitis and 1 of cholangitis were accompanied by gallstones, while the other 5 were acalculous. The treatment duration was significantly shorter in patients with PBI than in those without (median: 44 days vs. 201 days, P = .02). Overall, 9 of 69 patients without PBI showed asymptomatic gallbladder subserosal edema. Lenvatinib-induced PBI developed in 11.5% of patients, leading to a significantly shorter treatment duration. Approximately 55.6% of the PBI cases were acalculous. The recognition of this phenomenon would aid physicians during treatment planning in the future.